SOSIALISASI PENGAWASAN PARTISIPATIF MASYARAKAT TERHADAP PEMILU 2024 DI DESA LAYA (Jurnal Pengabdian Kepada Masyarakat (ABDIMAS) Universitas Baturaja, 2023)
The purpose of the socialization that we have carried out on May 16, 2023 is to provide an understanding to the people of Laya Village regarding welcoming the 2024 elections regarding community participatory monitoring of the 2024 elections. Where the community plays an important role in the implementation of elections because society is an object in influencing the quality of general elections in legislative and executive bodies. Because if there is a lack of the level of public participation in supervising elections, there will be violations in the electoral process. Where in the socialization process this provides space for discussion to the public regarding the material that has been submitted, namely about the role of the community in election supervision. During the discussion, several questions were asked to the public (audience) to measure the public's understanding of the material presented by the speaker. The community was very enthusiastic to answer the questions posed by the speakers with various answers according to the opinions of each community (audience).